2001
DOI: 10.1016/s0022-5347(05)65921-6
|View full text |Cite
|
Sign up to set email alerts
|

Can Standard Open Pediatric Urological Procedures Be Performed on an Outpatient Basis?

Abstract: Our experience shows that standard open pediatric urological procedures may be performed safely and comfortably on an outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Only children with lack of improvement in hydronephrosis underwent diuretic nuclear renography. 13 We assessed the primary outcome, intra-and postoperative complications (subdivided by timing before and after 3 months), and severity of complication according to the Clavien-Dindo Classification system. 14 Ethics approval for this study was obtained by our institutional Research Ethics Board.…”
Section: Methodsmentioning
confidence: 99%
“…Only children with lack of improvement in hydronephrosis underwent diuretic nuclear renography. 13 We assessed the primary outcome, intra-and postoperative complications (subdivided by timing before and after 3 months), and severity of complication according to the Clavien-Dindo Classification system. 14 Ethics approval for this study was obtained by our institutional Research Ethics Board.…”
Section: Methodsmentioning
confidence: 99%
“…C'est dire l'important potentiel qui existe au sein de nos structures. Le recueil d'événements indésira-bles et la politique d'amélioration continue de la qualité et de la gestion du risque chirurgical devraient permettre dans les années à venir d'élargir les indications de la chirurgie ambulatoire [30] et de la proposer avec sécurité à des patients de plus en plus jeunes.…”
Section: Discussionunclassified
“…The open technique has a success rate of more than 90%. 2 Open procedures usually require a hospital stay of 1 to 6 days, but Sprunger et al 3 found that standard open pediatric procedures could be performed safely on an outpatient basis.…”
Section: Intravesical Proceduresmentioning
confidence: 99%
“…Caudal anesthesia minimizes the need for inhalation agents, and therefore decreases the occurrence of postoperative nausea and vomiting. 3 …”
Section: Intraoperative Carementioning
confidence: 99%
See 1 more Smart Citation